Tuning the microstructure, martensitic transformation and superelastic properties of EBF3-fabricated NiTi shape memory alloy using interlayer remelting - Li, Binqiang (2022)
This work was supported by the National Natural Science Foundation of China (Grant no. 51871075 , 52171034 , and 52101037 ), Heilongjiang Postdoctoral Fund (Grant no. LBH-Z20139 ) and the Foundation of National Key Laboratory for Precision Hot Processing of Metals ( JCKYS2022603C003 ). JPO acknowledges Fundação para a Ciência e Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). Publisher Copyright: © 2022 The Authors